TINDAK TUTUR DIREKTIF DALAM RUBRIK READERâS FORUM DI THE JAKARTA POST - , SUFIL LAILIYAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study examines directive speech act in Readerâs Forum rubric of The Jakarta Post. The aims of this study are to explain type of directive speech act in Readerâs Forum rubric of The Jakarta Post, meaning of directive speech act in Readerâs Forum rubric of The Jakarta Post, and politeness strategy used in Readerâs Forum rubric of The Jakarta Post. This study uses descriptive qualitative approach. Some methods used in this study. First, the data were collected by using observation method. Second, the data were analyzed by using contextual method. Third, In presenting the result of data analysis, the researcher used an informal method of presentation. The results of this study are as follow. First, there are three types of directive speech acst